Comparison of Bolton’s Ratios in a Sample of Iraqi and Egyptian Populations - Al-Duliamy, Munad J.; Othman, Samer S.; Hussien, Farouk A. (Journal of Baghdad College of Dentistry, 2016)
Background: The objective of this study was to investigate the possibility of standardizing the Bolton ratio analysis as a diagnostic measure for both Iraqi and Egyptian orthodontic populations within three Angle' classification groups.Materials and methods: Two hundred forty pretreatment study casts (one hundred twenty of each population) were included in this study and divided into three Angle' classification groups. The mesiodistal crown diameters of all teeth were measured for computing the anterior and total Bolton ratios. Analysis of variance was performed to compare the mean ratios of Bolton analysis as a function of the Angle classification.HSD test was used to specify the classes of malocclusion that have significant differences.Results: No statistically significant differences were determined in the mean values of the anterior ratio among the angle classification groups in both Iraqi and Egyptian populations. No statistically significant differences were determined in the mean values of the overall ratio among the angle classification groups in Iraqi population. While there were statistically significant differences in the mean values of overall ratio among the angle classification groups in Egyptian population. This difference is specified with in class II malocclusion of Egyptian population. Conclusion: Anterior Bolton ratio can be standardized for both Iraqi and Egyptian orthodontic populations. While the overall ratio can be standardized only in class I and III malocclusions of both populations.